Tanggung Jawab Pengangkut terhadap Bagasi Bermasalah di Unit Lost and Found PT.Gapura Angkasa Cabang Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Ashari Rahman (Jurnal Transformasi Bisnis Digital, 2025)
PT Gapura Angkasa is one of the aviation companies whose business includes ground handling services. At Zainuddin Abdul Madjid Lombok International Airport, PT Gapura Angkasa handles ground handling for Garuda, Citilink, and Sriwijaya Air. Aircraft essentially transport passengers, baggage, cargo, and mail. Airlines are responsible for checked baggage entrusted by passengers. Regarding baggage, many passengers often experience issues such as lost, damaged, delayed, or mixed-up baggage. The unit responsible for handling problematic baggage is the Lost and Found unit. This research aims to evaluate the performance of the Lost and Found Unit in managing baggage issues. The study uses a qualitative method. The subjects of this research are the Lost and Found Unit at PT Gapura Angkasa Pura, Zainuddin Abdul Madjid Lombok International Airport Branch. Data for the research is obtained from primary sources, including observations and interviews, and secondary sources, such as photos/images and company records as well as Standard Operating Procedures (SOPs). Data credibility is tested through triangulation. Data analysis is performed through data reduction, data examination, and conclusion drawing. The research results show that the responsibility of the carrier towards problematic baggage at the Lost and Found Unit of PT Gapura Angkasa is carried out comprehensively, including steps for receiving reports, identifying, documenting, storing, and coordinating with airlines according to the applicable Standard Operating Procedures. However, there are still challenges, such as delays in tracking and returning baggage that need improvement. The carrier's responsibility for problematic baggage is in line with the regulations stipulated in PM No. 77 of 2011 concerning the procedures for managing and the responsibility for problematic baggage, including handling damaged, delayed, and lost baggage.